Comparisons of Herbicide Treated and Cultivated Herbicide-Resistant Corn - H. Arnold Bruns; Hamed K. Abbas (International Journal of Agronomy)
Four glyphosate resistant corn (Zea mays L.) hybrids, a glufosinate-ammonium resistant hybrid, and a conventional atrazine resistant hybrid gown at Stoneville, MS in 2005, 2006, and 2007 with furrow irrigation were treated with their respective herbicides and their growth, yield, and mycotoxin incidence were compared with untreated cultivated plots. Leaf area index (LAI) and dry matter accumulation (DMA) were collected on a weekly basis beginning at growth stage V3 and terminating at anthesis. Crop growth rates (CRGs) and relative growth rates (RGRs) were calculated. Plots were later harvested, yield and yield component data collected, and kernel samples analyzed for aflatoxin and fumonisin. Leaf area index, DMA, CRG, and RGR were not different among the herbicide treated plots and from those that were cultivated. Curves for LAI and DMA were similar to those previously reported. Aflatoxin and fumonisin were relatively low in all plots. Herbicide application or the lack thereof had no negative impact on the incidence of kernel contamination by these two mycotoxins. Herbicides, especially glyphosate on resistant hybrids, have no negative effects on corn yields or kernel quality in corn produced in a humid subtropical environment.